Role of the complex enzyme immunoassay testing in diagnosing uveitis in the presence of herpetic infection (Ukrainian Journal of Ophthalmology, 2026)
Background: In recurrent uveitis, establishing whether any herpetic infection has played an etiological or triggering role in the disease is important for selecting the appropriate treatment.Purpose: To assess the results of complex enzyme immunoassay testing (CEIAT) performed for patients with both uveitis and herpes simplex virus (HSV) infection in the process of treatment.Materials and Methods: In 73 uveitis patients, the CEIAT was used to determine serum levels of anti?HSV-IgМ and anti?HSV-IgG antibodies (Ab) to herpes simplex virus type 1 and type 2 (HSV1&2), IgG class Ab to nonstructural early viral antigens of HSV1&2, and the avidity of specific IgG Ab to HSV1&2.Results: The most common etiology of uveitis was herpetic infection (25.7%). In 74.3% of cases, HSV played a triggering role. The following three types of specific immunity were registered: (1) significantly (р
Keywords: uveitides; herpes simplex virus; complex enzyme immunoassay testing